PENGEMBANGAN EKONOMI BERBASIS MARITIM DI PROVINSI BANTEN - Bani Adi Darma (Jurnal Ekonomi-Qu, 2019)
The utilization of the maritime sector potential in Banten Province needs to be carried out professionally and comprehensively so that it can encourage sustainable economic development in Banten Province. This article discusses the potential and strategy for developing a maritime-based economic potential in Banten Province. Banten Province applies three approaches in achieving sustainable development, namely economic, socio-cultural and environmental aspects as a whole. The three approaches need to be derived in the form of goals and objectives so that a big vision of the sustainable development of Banten Province can be achieved. In the maritime sector, the programs and indicators that have been developed in measuring the achievements set out in the Regional Development Work Plan (RKPD) 2018 have alluded to these three aspects. However, there needs to be a review of strategies and policies to achieve the goals of sustainable development in the maritime sector. Therefore, the preparation of the Banten Province Maritime-Based Economic Development must be carried out to support the Banten Province's medium-term development plan from 2018-2022